Pneumocephalus in five horses. (23rd October 2012) - Dunkel, B.; Corley, K. T. T.; Johnson, A. L.; Witte, T. H.; Leitch, M.; Marr, C. M.; Weller, R.
Summary Pneumocephalus is occasionally encountered in horses but poorly described in the literature. The study aimed to describe historical, clinical and diagnostic imaging findings and outcome in horses to increase the awareness and recognition of the condition amongst equine practitioners, allowing appropriate management of these cases. Cases of pneumocephalus from 4 participating institutions were identified and case details extracted from the medical records. Five cases of pneumocephalus were identified. Head trauma with suspected or confirmed fractures of the sinuses was the underlying cause in 4 cases, while the remaining horse was thought to have developed pneumocephalus secondary to sinusitis or trauma. Diagnosis was established radiographically in 4 cases and by computed tomography in a fifth. Gas was noted between the cranial vault and the brain, in the lateral ventricles, in the brain parenchyma and within the cranial cervical canal. The gas accumulation resolved gradually in all horses and did not appear independently to result in neurological compromise. Long‐term outcome was available for 3 cases, 2 of which were ultimately subjected to euthanasia due to neurological deficits. Pneumocephalus is a possible consequence of head trauma or sinusitis in horses; although the finding is frequently incidental, it has the potential to develop into a life‐threatening complication. Imaging the complete skull and cranial cervical spine is important to allow identification and appropriate management of these cases. The use of computed tomography enables easier identification and localisation of the gas accumulation within the central nervous system.